2015
DOI: 10.1037/a0038665
|View full text |Cite
|
Sign up to set email alerts
|

The complex nature of family support across the life span: Implications for psychological well-being.

Abstract: This study examines the complex role of family networks in shaping adult psychological well-being over time. We examine the unique and interactive longitudinal influences of family structure (i.e., composition and size) and negative family relationship quality on psychological well-being among young (aged 18-34), middle-aged (aged 35-49), and older adults (aged 50+). A sample of 881 adults (72% White; 26% Black) was drawn from the longitudinal Social Relations, Age and Health Study. Structural equation modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 61 publications
8
51
1
Order By: Relevance
“…Patients with different levels of family support had different levels of preoperative well‐being ( p < .001); the preoperative well‐being of patients who were very satisfied with the family support that they received appeared to be greater than that of patients with lower satisfaction with their received level of family support ( p < .001). This finding is in line with past studies (Fuller‐Iglesias, Webster, & Antonucci, ; Nguyen, Chatters, Taylor, & Mouzon, ). Fuller‐Iglesias et al () found significant correlations between family support, depression and psychological well‐being; patients with more family support were more likely to have greater psychological well‐being, whereas more negative emotions caused by the family lead to more depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients with different levels of family support had different levels of preoperative well‐being ( p < .001); the preoperative well‐being of patients who were very satisfied with the family support that they received appeared to be greater than that of patients with lower satisfaction with their received level of family support ( p < .001). This finding is in line with past studies (Fuller‐Iglesias, Webster, & Antonucci, ; Nguyen, Chatters, Taylor, & Mouzon, ). Fuller‐Iglesias et al () found significant correlations between family support, depression and psychological well‐being; patients with more family support were more likely to have greater psychological well‐being, whereas more negative emotions caused by the family lead to more depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with past studies (Fuller‐Iglesias, Webster, & Antonucci, ; Nguyen, Chatters, Taylor, & Mouzon, ). Fuller‐Iglesias et al () found significant correlations between family support, depression and psychological well‐being; patients with more family support were more likely to have greater psychological well‐being, whereas more negative emotions caused by the family lead to more depressive symptoms. Nguyen et al () conducted a study among 837 older people and discovered that family intimacy is associated with life satisfaction and well‐being, and good family relationships can both enhance and be detrimental to well‐being.…”
Section: Discussionsupporting
confidence: 93%
“…Social networks contribute to ageing in place directly, as providers of social support (Burt, ; Kahn & Antonucci, ) and indirectly, functioning as a buffer for effects of stressful events (Krause, ) and more generally as enablers of health and well‐being (Berkman, Glass, Brissette, & Seeman, ; Cohen & Wills, ; Cornwell & Laumann, ; Freund & Baltes, ; Huber et al, ; Jowkar, Friborg, & Hjemdal, ; Kawachi, ; Seeman, Lusignolo, Albert, & Berkman, ; Uchino, Cacioppo, & Kiecolt‐Glaser, ). Literature on older adults’ social network change indicates that social networks of older adults remain stable (Bowling, Grundy, & Farquhar, ; Conway, Magai, Jones, Fiori, & Gillespie, ; van Tilburg, ) or decline (Fuller‐Iglesias, Webster, & Antonucci, ; Huxhold, Fiori, & Windsor, ; Reinhardt, Boerner, & Benn, ), but rarely grow. Other common findings include a loss of friends and a relatively increasing share of family members within networks (Bowling et al, ; Conway et al, ; Fuller‐Iglesias et al, ; Reinhardt et al, ) and the ending of relationships without frequent contact or with little support (‘peripheral relations’) (Kahn & Antonucci, ; Klein Ikkink & van Tilburg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Literature on older adults’ social network change indicates that social networks of older adults remain stable (Bowling, Grundy, & Farquhar, ; Conway, Magai, Jones, Fiori, & Gillespie, ; van Tilburg, ) or decline (Fuller‐Iglesias, Webster, & Antonucci, ; Huxhold, Fiori, & Windsor, ; Reinhardt, Boerner, & Benn, ), but rarely grow. Other common findings include a loss of friends and a relatively increasing share of family members within networks (Bowling et al, ; Conway et al, ; Fuller‐Iglesias et al, ; Reinhardt et al, ) and the ending of relationships without frequent contact or with little support (‘peripheral relations’) (Kahn & Antonucci, ; Klein Ikkink & van Tilburg, ). These changes in social networks, some of which can be interpreted as life events, challenge ageing in place because they are negatively associated with older adults’ health and well‐being (Ellwardt, van Tilburg, Aartsen, Wittek, & Steverink, ; Ellwardt, van Tilburg, & Aartsen, ; Kelly et al, ; Krause, ) and they affect support needs and resources (Guiaux, van Tilburg, & Broese van Groenou, ; Tomassini et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies indicate that strong family support networks are protective of mental health (Fuller‐Iglesias, Webster, & Antonucci, ; Lee & Szinovacz, ; Nguyen, Taylor, et al., ). For instance, research by Turvey et al.…”
Section: Introductionmentioning
confidence: 99%